A STUDY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF ENGLISH STUDY PROGRAM, UNIVERSITAS RIAU IN COMPREHENDING NARRATIVE TEXTS - Asmita, Gusni Nur; Ras, Fakhri; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This descriptive research is aimed at finding out the ability of the first year students of English Study Program, Universitas Riau in comprehending narrative texts. The population of the students were about 118 students. The sample were chosen by using cluster sampling technique, the sample size was as big as 78 students out of 118 students. The instrument of the research was a multiple choices test about narrative texts. The result shows that the mean score of the test of the first year students of English Study Program Universitas Riau is 73.77, categorized as good level. Based on the classification of students scores, there are 14 students (17%) are in excellent level, 50 students (64.1%) are in good level, 13 students (16.3%) students are in mediocre level and 1 students (1.3%) is in poor level. The lowest score of the components of the test is finding the generic structures of narrative text with the mean score 67.95, considered as good level. Meanwhile, the highest score of the components is finding references with the mean score 82.05, considered as excellent level. Therefore, it can be concluded that the ability of the first year students’ of English Study Program, Universitas Riau, is in the range of good level.Key Words: Ability, Comprehending, Narrative Texts.